Multiletramentos e ubiquidade em grupos de aprendizagem de língua inglesa no Facebook: possibilidades e limitações - Queiroz, Anita Cristina da Silva (Universidade Federal do Tocantins, 2021)
Based on the observation of the BBC English language learning group on the social network Facebook, we conducted a descriptive documentary research on the functioning of groups for English language learning in this social network. We intend to raise the contributions and limitations of this resource to the classroom - or beyond it. We live in the age of digital communication, in which children are digital natives (PRENSKI, 2001) and can easily navigate on web 2.0. Not to link the teaching-learning process to digital technologies would be to stagnate education. Going into the context of children and young people promoting multiliteracies (ROJO, 2014; COPE; KALANTZIS, 2000) is transformative and motivating for students who are often in standardized classes carried out only on the blackboard and/or with textbooks followed to the letter. By choosing the social network Facebook, we observe the autonomous, but also collaborative modes of learning groups, emphasizing the possibilities of learning anywhere, approaching the current reality of the students, making the virtual environment also a pedagogical apparatus; thus thinking about the teaching-learning process at hand beyond the classroom, providing flexibility of time and place in mobile and ubiquitous learning.